Assistance For Students to Improving Islamic Religious And Economic Education In Islamic Boarding Schools in Indonesia - Katni Katni; Dato' Ab Halim Tamuri; Adib Khusnul Rois; Femi Astika Candra Chairani; Syamsul Arifin (International Journal Of Community Service, 2024)
The Ahmad Dahlan Qur'an Memorization Islamic Boarding School in Ponorogo Regency is an Islamic boarding school under the auspices of the Muhammadiyah organization, which has a different level of academic quality compared to modern boarding school students, including the following: 1) Mastery of the yellow books or classical Islamic literature in Arabic across various religious disciplines. 2) In- depth knowledge of Arabic grammar or Nahwu, Sharaf, balaghah (meaning, bayan, badi’), and logic, as these subjects are studied seriously and occupy a significant portion of the modern boarding school curriculum. 3) Proficiency in memorizing the Qur'an. 4). Entrepreneurship program for students. Students are required to study Islam comprehensively to develop a religious character. The pesantren emphasizes values such as discipline, a sense of responsibility, independence, simplicity, and honesty. In addition, they are also taught about entrepreneurship. It is hoped that the students will develop a character that can master their faith and possess the skills for independence after graduating from the pesantren.